Parenting Skills as The Closest Teacher to Early Childhood at Home - Amin, Adam Aliathun; Eliasa , Eva Imania (JURNAL PENDIDIKAN USIA DINI, 2023)
Parents play an important role in the development of their children. This research reflects the role of parents in developing children. Through four stages of identification, screening, eligibility, and acceptable results, this method uses a systematic literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) method. The findings from the fourteen articles examined show that parenting skills play an important role in a child's growth and development from birth to death. The determining factor in the development of physical, motoric, moral, language, social-emotional, and life skills aspects is the role of both parents as important teachers for children from birth to adulthood. Parents can also use a variety of parenting strategies and skills, many of which they have learned throughout their lives and passed on to their children, to help their children grow. Keywords: Role of Parents, Child Development, first education for children References: Albanese, A. M., Russo, G. R., & Geller, P. A. (2019). The role of parental self‐efficacy in parent and child well‐being. Child Care Health Dev, 45(3), 333–363. https://doi.org/10.1111/cch.12661. Almås, I., Cappelen, A. W., Sørensen, E. Ø., Tungodden, B., Alm, I., & Tungodden, B. (2010). Fairness and the Development of Inequality Acceptance Supporting materials for “ Fairness and the development of inequality acceptance .” Science, 328(5982), 1176–1178. https://doi.org/10.1126/science.1187300. Ahmadi, Abu. 2004. Psikologi Belajar. Jakarta : Rineka Cipta. Ahmetoglu, E., Acar, I. H., & Ozturk, M. A. (2022). Parental involvement and children’s peer interactions. Current Psychology, 41(7), 4447–4456. https://doi.org/10.1007/s12144-020-00965-0. Andhika, M. R. (2021). Peran Orang Tua Sebagai Sumber Pendidikan Karakter Bagi Anak Usia Dini. At-Ta’Dib: Jurnal Ilmiah Prodi Pendidikan Agama Islam, 13(1), 73. https://doi.org/10.47498/tadib.v13i01.466. Arthur, A. E., Bigler, R. S., Liben, L. S., Gelman, S. A., & Ruble, D. N. (2008). Gender stereotyping and prejudice in young children. In S. R. Levy & M. Killen (Eds.), Intergroup attitudes and relations in childhood through adulthood (pp. 66–86). New York, NY: Oxford University Press. Aydin, G., Margerison, C., Worsley, A., & Booth, A. (2021). Parents’ and teachers’ views of the promotion of healthy eating in Australian primary schools. BMC Public Health, 21(1), 1–12. https://doi.org/10.1186/s12889-021-11813-6. Baumard, N., Mascaro, O., & Chevallier, C. (2012). Preschoolers Are Able to Take Merit into Account When Distributing Goods. 48(2), 492–498. https://doi.org/10.1037/a0026598. Benozio, A., & Diesendruck, G. (2015). Parochialism in preschool boys ’ resource allocation. Evolution and Human Behavior, 36(4), 256–264. https://doi.org/10.1016/j.evolhumbehav.2014.12.002. Berthelot, N., Lemieux, R., Garon-Bissonnette, J., Lacharité, C., & Muzik, M. (2019). The protective role of mentalizing: Reflective functioning as a mediator between child maltreatment, psychopathology and parental attitude in expecting parents. Child Abuse and Neglect, 95(April). https://doi.org/10.1016/j.chiabu.2019.104065. Bigler, R. S., & Liben, L. S. (2006). A Developmental Intergroup Theory Of Social Stereotypes And Prejudice. Advances in Child Development and Behavior, 16, 162–166. https://doi.org/https://doi.org/10. 1111/j.1467-8721.2007.00496.x. Bigler, R. S., & Liben, L. S. (2007). Developmental Intergroup Theory: Explaining and reducing children’s social stereotyping and prejudice. Association for Psychological Science, 16(3), 162–166. https://doi.org/https://doi.org/10. 1111/j.1467-8721.2007.00496.x. Blair, C., & Diamond, A. (2008). Biological processes in prevention and intervention: The promotion of self-regulation as a means of preventing school failure. Development and Psychopathology, 20(3), 899–911. https://doi.org/10.1017/S0954579408000436. Chacko, A., Jensen, S. A., Lowry, L. S., Cornwell, M., Chimklis, A., Chan, E., Lee, D., & Pulgarin, B. (2016). Engagement in Behavioral Parent Training: Review of the Literature and Implications for Practice. Clinical Child and Family Psychology Review, 19(3), 204–215. https://doi.org/10.1007/s10567-016-0205-2 Cheal, D. J. (1988). In Intergenerational Transfers. Int’l. J. Aging And Human Development, 26(4), 261–273. https://doi.org/10.2190/V2E8-UEAT-5MJ7-UQ6F. Chernyak, N., & Kushnir, T. (2013). Giving Preschoolers Choice Increases Sharing Behavior. Psychological Science, 24(10), 1971–1979. https://doi.org/10.1177/0956797613482335. Coleman, M., Ganong, L. H., Hans, J. D., Sharp, E. A., & Rothrauff, T. C. (2005). Filial Obligations in Post-Divorce Stepfamilies Filial Obligations in Post-Divorce Stepfamilies. Journal of Divorce & Remarriage, 43(3/4), 37–41. https://doi.org/10.1300/J087v43n03. Cvencek, D., & Meltzoff, A. N. (2015). Developing Implicit Social Cognition In Early Childhood : Methods, phenomena, prospects. The Routledge International Handbook of Young Children’s Thinking and Understanding, 43–53. https://www.researchgate.net/publication/343658204_4_Developing_implicit_social_cognition_in_early_childhood_Methods_phenomena_prospects. Davis-Kean, P. E., Tighe, L. A., & Waters, N. E. (2021). The Role of Parent Educational Attainment in Parenting and Children’s Development. Current Directions in Psychological Science, 30(2), 186–192. https://doi.org/10.1177/0963721421993116. Damon, W. (1977). The social world of the child. San Francisco, CA: Jossey-Bass. Dunfield, K. A., Kuhlmeier, V. A., & Murphy, L. (2013). Children ’ s Use of Communicative Intent in the Selection of Cooperative Partners. PLoS ONE, 8(4), 1–6. https://doi.org/10.1371/journal.pone.0061804. Eagly, A. H., & Wood, W. (2017). Social Role Theory (Issue January 2012). https://doi.org/10.4135/9781446249222.n49. Fadillah, M. (2012). Desain Pembelajaran PAUD Tinjauan Teoritik & Praktik. Ar-Ruzz Media. Fan, R., Ruoyu, L., Chang, G., Yongling, H., Haiyan, H., Chunyan, P., Xinzhu, W., & Yuhui, W. (2022). Association of mothers’ adverse childhood experiences and parenting styles with emotional behavior problems in preschool children. Sch. Health China, 43(8), 1134–1138. https://doi.org/10.16835/j.cnki.1000-9817.2022.08.004. Fardiansyah, H. (2022). Manajemen Pendidikan (Tinjaun Pada Pendidikan Formal). Bandung: Widina Media Utama. Feng, L., Zhang, L., & Zhong, H. (2021). Perceived parenting styles and mental health: The multiple mediation effect of perfectionism and altruistic behavior. Psychology Research and Behavior Management, 14, 1157–1170. https://doi.org/10.2147/PRBM.S318446. Fikriyah, S., Mayasari, A., Ulfah, U., & Arifudin, O. (2022). Peran Orang Tua Terhadap Pembentukan Karakter Anak Dalam Menyikapi Bullying. Jurnal Tahsinia, 3(1), 11–19. https://doi.org/10.57171/jt.v3i1.306. Finch, J. (1989). Family Obligations and Social Change. Cambridge: Polity Press. Fiske, S. T., Cuddy, A. J. C., & Glick, P. (2002). A Model of ( Often Mixed ) Stereotype Content : Competence and Warmth Respectively Follow From Perceived Status and Competition. Of Personality and Social Psychology, 82(6), 878–902. https://doi.org/10.1037//0022-3514.82.6.878. Florean, I. S., Dobrean, A., Păsărelu, C. R., Georgescu, R. D., & Milea, I. (2020). The Efficacy of Internet-Based Parenting Programs for Children and Adolescents with Behavior Problems: A Meta-Analysis of Randomized Clinical Trials. Clinical Child and Family Psychology Review, 23(4), 510–528. https://doi.org/10.1007/s10567-020-00326-0. Ganong, L., & Coleman, M. (2006). Patterns of exchange and intergenerational responsibilities after divorce and remarriage. Journal of Aging Studies, 20, 265–278. https://doi.org/10.1016/j.jaging.2005.09.005. Hapsari, D. I., Dewi, R. R. K., & Selviana. (2019). Determinan Kejadian Stunting Pada Balita Di Wilayah 3T (Tertinggal , Terdepan, dan Terluar). Jurnal Publikasi Kesehatan Masyarakat Indonesia, 6(2), 72–78. https://doi.org/10.20527/jpkmi.v6i2.7456. Hartman, K. M., Ratner, N. B., & Newman, R. S. (2016). Infant-directed speech ( IDS ) vowel clarity and child language outcomes *. Child. Lang, 44, 1140–1162. https://doi.org/10.1017/S0305000916000520. Hofmann, V., & Müller, C. M. (2021). Learning , Culture and Social Interaction Language skills and social contact among students with intellectual disabilities in special needs schools. Learning, Culture and Social Interaction, 30(PA), 100534. https://doi.org/10.1016/j.lcsi.2021.100534. Houdt, K. Van, Kalmijn, M., & Ivanova, K. (2018). Family Complexity and Adult Children ’ s Obligations : The Role of Divorce and Co-Residential History in Norms to Support Parents and Step-Parents. European Sociological Review, 34(2), 169–183. https://doi.org/10.1093/esr/jcy007. House, B. R., Silk, J. B., Henrich, J., Barrett, H. C., Scelza, B. A., Boyette, A. H., Hewlett, B. S., Mcelreath, R., & Laurence, S. (2013). Ontogeny of prosocial behavior across diverse societies. Proceedings of the National Academy of Sciences, 110(36), 14586–14591. https://doi.org/https://doi.org/10.1073/pnas.1221217110. Irma, C. N., Nisa, K., & Sururiyah, S. K. (2019). Keterlibatan Orang Tua dalam Pendidikan Anak Usia Dini di TK Masyithoh 1 Purworejo. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 3(1), 214. https://doi.org/10.31004/obsesi.v3i1.152. Jackson, L. A., Witt, E. A., Fitzgerald, H. E., VonEye, A., & Zhao, Y. (2011). Perceptions of parent behavior and children’s information technology use. In T. Bastiaens, & M. Ebner (Eds.). Proceedings of ED-MEDIA 2011–World Conference on Educational Multimedia, Hypermedia & Telecommunications (pp. 3864–3869). Lisbon, Portugal: Association for the Advancement of Computing in Education (AACE). Jatiningsih, O., Habibah, S. M., Wijaya, R., & Sari, M. M. K. (2021). Peran Orang Tua Dalam Pemenuhan Hak Pendidikan Anak Pada Masa Belajar Dari Rumah. Jurnal Ilmu Sosial Dan Humaniora, 10(1), 147. https://doi.org/10.23887/jish-undiksha.v10i1.29943. Jeon, H. J., Peterson, C. A., Luze, G., Carta, J. J., & Clawson Langill, C. (2020). Associations between parental involvement and school readiness for children enrolled in Head Start and other early education programs. Children and Youth Services Review, 118(April), 105353. https://doi.org/10.1016/j.childyouth.2020.105353. Juniarti, Y., & Nurlaeni. (2017). Peran Orang Tua Dalam Mengembangkan Kemampuan Bahasa Pada Anak Usia 4-6 Tahun. Jurnal Pelita PAUD, 2(1), 51–62. https://doi.org/https://doi.org/10.33222/pelitapaud.v2i1.196. Kanngiesser, P., & Warneken, F. (2012). Young Children Consider Merit when Sharing Resources with Others. PLoS ONE, 7(8), 1–5. https://doi.org/10.1371/journal.pone.0043979. Kienbaum, J., & Wilkening, F. (2009). European Journal of Children ’ s and adolescents ’ intuitive judgements about distributive justice : Integrating need , effort , and luck. European Journal of Developmental Psychology, 6(4), 481–498.https://doi.org/10.1080/17405620701497299. Koenig, A. M., & Eagly, A. H. (2014). Evidence for the Social Role Theory of Stereotype Content : Observations of Groups ’ Roles Shape Stereotypes. Journal of Personality and Social Psychology, 107(3), 371–392. https://doi.org/10.1037/a0037215. Latifa, U. (2017). Perkembangan pada Anak Sekolah Dasar: Masalah dan Perkembangannya. Academica: Journal of Multidisciplinary Studies, 1(2), 185–196. https://ejournal.uinsaid.ac.id/index.php/academica/article/download/1052/297. Lee, E. J., & Sun, H. (2018). Gender Differences in Smartphone Addiction Behaviors Associated With Parent Y Child Bonding , Parent Y Child Communication , and Parental Mediation Among Korean Elementary School Students. Journal of Addictions Nursing, 29(4), 244–254. https://doi.org/10.1097/JAN.0000000000000254. Lilawati, A. (2020). Peran Orang Tua dalam Mendukung Kegiatan Pembelajaran di Rumah pada Masa Pandemi. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(1), 549. https://doi.org/10.31004/obsesi.v5i1.630. Lin, X., Liao, Y., & Li, H. (2022). Parenting Styles and Social Competence in Chinese Preschoolers: A Moderated Mediation Model of Singleton and Self-regulation. Early Education and Development, 33(3), 437–451. https://doi.org/10.1080/10409289.2021.1940643. Maifani. (2016). Peranan Orang Tua dalam Pembentukan Karakter Anak Sejak Dini di Desa Lampoh Tarom Kecamatan Kuta Baro Kabupaten Aceh Besar. Aceh: UIN Ar-Raniry Banda Aceh. Malti, T., Gummerum, M., Ongley, S., Chaparro, M., Nola, M., & Bae, N. Y. (2016). ‘“ Who is worthy of my generosity ?”’ Recipient characteristics and the development of children ’ s sharing. International Journal of Behavioral Development, 40(1), 31–40. https://doi.org/10.1177/0165025414567007. Martin, C. L., & Ruble, D. (2004). Current Directions in Psychological Science Children ’ s Search for Gender Cues Cognitive Perspectives on Gender Development. Current Directions in Psychological Science, 13(2), 67–70. https://doi.org/10.1111/j.0963-7214.2004.00276.x. Morgan, G., Curtin, M., & Botting, N. (2021). Infant Behavior and Development The interplay between early social interaction , language and executive function development in deaf and hearing infants. Infant Behavior and Development, 64(June), 101591. https://doi.org/10.1016/j.infbeh.2021.101591. Niu, G., Chai, H., Li, Z., Wu, L., & Sun, X. (2019). Online Parent-Child Communication and Left-Behind Children ’ s Subjective Well-Being : the Effects of Parent-Child Relationship and Gratitude. Child Indicators Research, 13(6). https://doi.org/https://doi.org/10.1007/s12187-019-09657-z. Ong, M. Y., Eilander, J., Saw, S. M., Xie, Y., Meaney, M. J., & Broekman, B. F. P. (2018). The influence of perceived parenting styles on socio-emotional development from pre-puberty into puberty. European Child and Adolescent Psychiatry, 27(1), 37–46. https://doi.org/10.1007/s00787-017-1016-9. Paulus, M. (2014). The early origins of human charity : developmental changes in preschoolers ’ sharing with poor and wealthy individuals. Frontiers in Psychology, 5, 1–10. https://doi.org/10.3389/fpsyg.2014.00344. Piotrowska, P. J., Tully, L. A., Lenroot, R., Kimonis, E., Hawes, D., Moul, C., Frick, P. J., Anderson, V., & Dadds, M. R. (2017). Mothers, Fathers, and Parental Systems: A Conceptual Model of Parental Engagement in Programmes for Child Mental Health—Connect, Attend, Participate, Enact (CAPE). Clinical Child and Family Psychology Review, 20(2), 146–161. https://doi.org/10.1007/s10567-016-0219-9. Popov, L. M., & Ilesanmi, R. A. (2015). Parent-Child Relationship : Peculiarities and Outcome. Review of European Studies, 7(5), 21–27. https://doi.org/10.5539/res.v7n5p253. Prabhawani, S. W. (2016). Pelibatan Orang Tua dalam Program Sekolah di TK Khalifah. Pendidikan Guru PAUD S-1, 5(2), 205–218. http://journal.student.uny.ac.id/ojs/index.php/pgpaud/article/view/1217. Procentese, F., Gatti, F., & Di Napoli, I. (2019). Families and social media use: The role of parents’ perceptions about social media impact on family systems in the relationship between family collective efficacy and open communication. International Journal of Environmental Research and Public Health, 16(24). https://doi.org/10.3390/ijerph16245006. Ratiwi, R. D., & Sumarni, W. (2020). Peran Orang Tua Dalam Pendampingan Belajar Daring. Cetta: Jurnal Ilmu Pendidikan,3(ISSN: 2686 6404), 304–309. https://proceeding.unnes.ac.id/index.php/snpasca/article/view/600/518. Rizzo, M. T., Elenbaas, L., Cooley, S., & Killen, M. (2016). Children’s Recognition of Fairness and Others’ Welfare in a Resource Allocation Task: Age Related Changes. Developmental Psychology, 52(8), 1307–1317. https://doi.org/https://doi.org/10.1037/dev0000134. Rossi, P. H. and Rossi, A. S. (1990). Of Human Bonding: Parent-Child Relations across the Life Course. New York: Aldine de Gruyter. Ruli, E. (2020). Tugas Dan Peran Orang Tua Dalam Mendidk Anak. Jurnal Edukasi Nonformal, vol.1(No.1), hlm.145. https://ummaspul.e-journal.id/JENFOL/article/view/428. Sabani, F. (2019). Perkembangan Anak - Anak Selama Masa Sekolah Dasar (6 - 7 Tahun). Didakta: Jurnal Kependidikan, 8(2), 89–100. https://doi.org/https://doi.org/10.58230/27454312.71. Salwiah, S., & Asmuddin, A. (2022). Membentuk Karakter Anak Usia Dini melalui Peran Orang Tua. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 6(4), 2929–2935. https://doi.org/10.31004/obsesi.v6i4.1945. Schmidt, M. F. H., & Sommerville, J. A. (2011). Fairness Expectations and Altruistic Sharing in 15-Month-Old Human Infants. PLoS ONE, 6(10). https://doi.org/10.1371/journal.pone.0023223. Scott-phillips, T. C. (2016). Pragmatics and the aims of language evolution. Psychonomic Bulletin & Review, 24(2), 186–189. https://doi.org/10.3758/s13423-016-1061-2. Shaw, A., Descioli, P., & Olson, K. R. (2012). Fairness versus favoritism in children ☆. Evolution and Human Behavior, 33(6), 736–745. https://doi.org/10.1016/j.evolhumbehav.2012.06.001. Shutts, K., Brey, E. L., Dornbusch, L. A., & Slywotzky, N. (2016). Children Use Wealth Cues to Evaluate Others. PLoS ONE, 11(3), 1–21. https://doi.org/10.1371/journal.pone.0149360. Smetana, J. G., & Rote, W. M. (2019). Adolescent – Parent Relationships : Progress , Processes , and Prospects. Annual Review of Developmental Psychology, 1, 41–68. https://doi.org/https://doi.org/10.1146/annurev-devpsych-121318-084903. Smith, C. E., Blake, P. R., & Harris, P. L. (2013). I Should but I Won ’ t : Why Young Children Endorse Norms of Fair Sharing but Do Not Follow Them. 8(3). https://doi.org/10.1371/journal.pone.0059510. Spilt, J. L., & Harrison, L. J. (2015). Language Development in the Early School Years : The Importance of Close Relationships With Teachers. Developmental Psychology, 51(2), 185–196. https://doi.org/10.1037/a0038540. Sri Asri, A. (2018). Hubungan Pola Asuh Terhadap Perkembangan Anak Usia Dini. Jurnal Ilmiah Sekolah Dasar, 2(1), 1. https://doi.org/10.23887/jisd.v2i1.13793. Stein, C. H., Wemmerus, V. A., Ward, M., Gaines, M. E., Freeberg, A. L., Jewell, T. C., Ward, M., Gaines, M. E., Freeberg, A. L., & Jewell, T. C. (1998). “Because They’re My Parents”: An Intergenerational Study of Felt Obligation and Parental Caregiving. Journal of Marriage and the Fam, 60(3), 611–622. https://doi.org/https://doi.org/10.2307/353532. Sugiyanto, W. P. (2015). Pengaruh Pola Asuh Orang Tua Terhadap Perilaku Prososial Siswa Kelas V Sd Se Gugus Ii Kecamatan Pengasih Kabupaten Kulon Progo Tahun Ajaran 2014/2015. Pendidikan Guru Sekolah Dasar, 15(4), 1–27. https://doi.org/10.31004/aulad.v3i1.53. Syahailatua, J., & Kartini, K. (2020). Pengetahuan ibu tentang tumbuh kembang berhubungan dengan perkembangan anak usia 1-3 tahun. Jurnal Biomedika Dan Kesehatan, 3(2), 77–83. https://doi.org/10.18051/jbiomedkes.2020.v3.77-83. Talango, S. R. (2020). Konsep Perkembangan Anak Usia Dini. Early Childhood Islamic Education Journal, 1(1), 92–105. https://doi.org/10.54045/ecie.v1i1.35. Taubah, M. (2016). Pendidikan Anak Dalam Keluarga Perspektif Islam Mufatihatut Taubah (Dosen STAIN Kudus Prodi PAI). JUrnal Pendidikan Agama Islam, 3(1), 109–136. https://doi.org/https://doi.org/10.15642/jpai.2015.3.1.109-136. Tocaimaza-Hatch, C. C., & Santo, J. (2020). Social interaction in the Spanish classroom : How proficiency and linguistic background impact vocabulary learning. Language Teaching Research, 27(5), 1–25. https://doi.org/10.1177/1362168820971468. Triandis, H. C. (2001). Individualism-Collectivism and Personality. Journal of Personality, 69(6), 907–924. https://doi.org/https://doi. org/10.1111/1467-6494.696169. Vieira, J. M., Matias, M., Ferreira, T., Lopez, F. G., & Matos, P. M. (2016). Parents ’ Work-Family Experiences and Children ’ s Problem Behaviors : The Mediating Role of the Parent – Child Relationship. Journal of Family Psychology, 30(4), 419–430. https://doi.org/http://dx.doi.org/10.1037/fam0000189. Wahidin. (2019). Peran Orang Tua Dalam Menumbuhkan Motivasi Belajar Anak Sekolah Dasar. Pancar, 3(1), 232–245. https://ejournal.unugha.ac.id/index.php/pancar/article/view/291. Wang, M., Wang, J., Deng, X., & Chen, W. (2019). Why are empathic children more liked by peers? The mediating roles of prosocial and aggressive behaviors. Personality and Individual Differences, 144(September 2018), 19–23. https://doi.org/10.1016/j.paid.2019.02.029. Wiresti, R. D., & Na’imah, N. (2020). Aspek Perkembangan Anak : Urgensitas Ditinjau dalam Paradigma Psikologi Perkembangan Anak. Aulad : Journal on Early Childhood, 3(1), 36–44. https://doi.org/10.31004/aulad.v3i1.53. Wood, W., & Eagly, A. H. (2012). Biosocial Construction of Sex Differences and Similarities in Behavior. In Advances in Experimental Social Psychology (1st ed., Vol. 46). Elsevier Inc. https://doi.org/10.1016/B978-0-12-394281-4.00002-7. Xia, X. (2023). Parenting style and Chinese preschool children’s pre-academic skills: A moderated mediation model of approaches to learning and family socioeconomic status. Frontiers in Psychology, 14(February), 1–9. https://doi.org/10.3389/fpsyg.2023.1089386. Xie, X., Chen, W., Zhu, X., & He, D. (2019). Parents’ phubbing increases Adolescents’ Mobile phone addiction: Roles of parent-child attachment, deviant peers, and gender. Children and Youth Services Review, 105(April), 104426. https://doi.org/10.1016/j.childyouth.2019.104426. Xie, Y., Shi, Z., Yin, L., & Lan, L. (2022). A Meta-Analysis of the Relationships between Chinese Parenting Styles and Child Academic Achievement. Best Evidence in Chinese Education, 12(1), 1589–1595. https://doi.org/10.15354/bece.22.ab009. Yang, N., Shi, J., Lu, J., & Huang, Y. (2021). Language Development in Early Childhood : Quality of Teacher-Child Interaction and Children ’ s Receptive Vocabulary Competency. Frontiers in Psychology, 12(July), 1–12. https://doi.org/10.3389/fpsyg.2021.649680. Zhang, W., Yu, G., Fu, W., & Li, R. (2022). Parental Psychological Control and Children’s Prosocial Behavior: The Mediating Role of Social Anxiety and the Moderating Role of Socioeconomic Status. International Journal of Environmental Research and Public Health, 19(18). https://doi.org/10.3390/ijerph191811691.